COINING LEGAL TERMS – A CASE STUDY OF POLISH AND GERMAN COMMERCIAL LAW - SIEWERT, Katarzyna (Comparative Legilinguistics, 2010)
Since the 1970s legal language as a language for special purposes has been a subject of growing interest among researchers. In the early period of scientific study specialised vocabulary was considered to be the essential element of a language for special purposes. Therefore, the first studies of legal language focused mainly on terminology. However, despite intensive research into the problems of terminology, forming terms in legal language remains an open area of scientific study. The article is an attempt at presenting different means that can be used in legal language to meet the demand for new terms, as well as showing the extent to which particular means are used in forming the terminology of Polish and German trade law. In this aspect the author also presents difficulties connected with understanding and proper usage of terms which an ordinary citizen can encounter when trying to comprehend complicated legal texts.